Financial stability with sovereign debt - Izumi, Ryuichiro (Journal of Financial Stability, 2020)
Are government guarantees or financial regulation a more effective way to prevent banking crises? I study this question in the presence of a negative feedback loop between the fiscal position of the government and the health of the banking sector. I construct a model of financial intermediation in which the government issues, and may default on, debt. Banks hold some of this debt, which ties their health to that of the government. The government's tax revenue, in turn, depends on the quantity of investment that banks are able to finance. I compare the effectiveness of government guarantees, liquidity regulation, and a combination of these policies in preventing self-fulfilling bank runs. In some cases, a combination of the two policies is needed to prevent a run. In other cases, liquidity regulation alone is effective and adding guarantees would make the financial system fragile.